Simulasi dosis serap kanker payudara dengan empat sudut penyinaran menggunakan teknik radioterapi konformal tiga dimensi - Wihantoro Wihantoro; Abdul Aziz Toyib; Aris Haryadi; Efita Perwira Adi (Jurnal Teras Fisika: Teori, Modeling, dan Aplikasi Fisika, 2022)
Cancer treatment using radiotherapy has several techniques. This study uses a three-dimensional conformal technique with four radiation directions at angles of 0°, 60°, 180°, and 240°. This study aims to determine the absorbed dose of breast cancer tissue using a three-dimensional conformal radiotherapy technique with the addition of a multileaf collimator (MLC) using a linear accelerator radiotherapy machine. The MLC is modeled in the form of a beam with 24 rods made in duplicate which is inserted in the middle of an empty space in the form of a cylinder with a diameter of 1.3 cm. The cancer tissue was modeled as a ball with a diameter of 3 cm located in the center of the left breast. The method used is the Monte Carlo method using the MCNPX Visual Editor software. The combined absorption dose for the four radiation directions showed the largest absorption dose was in cancer tissue at 2 Gy, while the organ that received the least absorption dose was the liver at 0.0054 Gy.